Penatalaksanaan Propioceptive Neuromuscular Facilitation (Pnf) Pada Kondisi Stroke Non Haemoragik Stadium Recovery Di Rsu Aisiyah Ponorogo - Abdurrahim, Ahmad; , Wahyuni, S.Fis., M.Kes (2015)
Background: Stroke is a cardiovascular disease that affects the main artery leading to and are in the brain. Stroke occurs when a blood vessel that carries oxygen and nutrients to the brain is blocked by a clot or a rupture so that the brain does not get the blood it needs. Stroke patients recovery stage causes abnormal muscle tone changes characterized by increased tone. With the abnormal postural tone in (spasticity) there will be a movement disorder that can result in the disruption of functional activity and can hinder and inhibit the emergence of balance. Objective: To investigate the implementation of the PNF in the case of non haemoragik stroke recovery stage can reduce spasticity, increase muscle strength, improve balance and coordination and to improve functional ability. Results: After treatment for 6 times the results obtained with the spasticity assessment scale asworth T1: 2 wrist flexors, finger flexors - finger 2, into T6: 1 wrist flexors, finger flexors - finger 2. Increased muscle strength with MMT occur in the flexor and extensor elbow showed T1: 1 elbow flexor, extensor elbow 1, becomes T6:: 2 elbow flexors, extensors elbow 2. Ability coordination and balance did not increase from T1 to T6. Increased functional activity with the Barthel index, T0: Total score of 75 to T6: 80. Conclusion: Giving PNF able to provide relaxation thereby affecting the decrease in the level of spasticity in patients with non haemoragik stroke. However spasticity could return if the intensity of exercise the patient is very less, able to provide facilitation to the muscles to contract, and thus can increase muscle strength and improve motor coordination, and in line with the development of motor and sensory in stroke patients, there will be an increase in functional activity. Keywords: Stroke, Propioceptive Neuromuscular Facilitation (PNF), Asworth Scale, Manual Muscle Testing (MMT), Barthel index.